Controlling the cooperative self-assembly of graphene oxide quantum dots in aqueous solutions1. Issue 71 (2nd August 2015) - Hassanzadeh, Salman; Adolfsson, Karin H.; Hakkarainen, Minna
<x xml:space="preserve">Abstract</x> The 3D supramolecular association behavior of the synthesized 2D graphene oxide quantum dots (GOQDs) could be smartly controlled in dilute aqueous solutions to tune their final properties.